(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study explored the benefits of e-learning technologies in business education programmes in universities by considering the concerns of the availability of the technologies. Two research questions and two hypotheses were raised and formulated respectively to guide the study. The study adopted a descriptive survey research design. The population of the study comprised 521 Business Education students at the University of Benin and Benson Idahosa University, out of which 100 students were used as a sample, using the disproportionate stratified random sampling technique. A structured questionnaire containing 17 items was the instrument used for data collection. Having validated the instrument, its reliability was determined using Cronbach’s alpha method, which yielded a coefficient 0.84. Data collected were analyzed using mean and standard deviation for the research questions, while t-test and Analysis of Variance (ANOVA) were used to test the hypotheses. The findings of the study revealed that students had several positive perceptions about e-learning technologies for enhancing business education programme to bridge the gap that exists between theories and practice in learning. However, availability of the e-learning resources is a concern because students perceived that the resources were not available in their institutions as expected. Based on the findings it was recommended that relevant shareholders in education should provide adequate e-learning technologies for the teaching and learning process of business education courses.